2018
DOI: 10.1016/j.jadohealth.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Race and Criminal Justice Involvement on Sexual Behaviors of Young Men Who Have Sex With Men

Abstract: We found that the intersection between race and criminal justice involvement plays a major role in sexual behaviors. More research is needed to understand why a history of arrest or incarceration has a much more profound effect on black MSM than on non-black MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The most common measure, reported by 28 studies (60%), was prevalence of incarceration history. Of these, 19 articles reported lifetime incarceration history estimates [11,12,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Eleven of these articles had estimates focused on BMSM of all ages (i.e., samples of all or primarily BMSM) [11, 28-31, 34-36, 40, 42, 43], five particularly among YBMSM [33,[37][38][39]44], one among BTW only [41], and two among both BMSM and BTW [12,32].…”
Section: Summary Of Included Articlesmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common measure, reported by 28 studies (60%), was prevalence of incarceration history. Of these, 19 articles reported lifetime incarceration history estimates [11,12,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Eleven of these articles had estimates focused on BMSM of all ages (i.e., samples of all or primarily BMSM) [11, 28-31, 34-36, 40, 42, 43], five particularly among YBMSM [33,[37][38][39]44], one among BTW only [41], and two among both BMSM and BTW [12,32].…”
Section: Summary Of Included Articlesmentioning
confidence: 99%
“…Of these, 19 articles reported lifetime incarceration history estimates [11,12,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Eleven of these articles had estimates focused on BMSM of all ages (i.e., samples of all or primarily BMSM) [11, 28-31, 34-36, 40, 42, 43], five particularly among YBMSM [33,[37][38][39]44], one among BTW only [41], and two among both BMSM and BTW [12,32]. Incarceration estimates focused on BMSM had values ranging from 25.5 to 84%, while those on YBMSM ranged from 2.4 to 53.5% [32,33,[37][38][39]44].…”
Section: Summary Of Included Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one study of a sample of 252 AAMSM recruited in nightclubs in North Carolina found those recently incarcerated were more likely to report insertive unprotected anal intercourse [5]. A longitudinal study of young MSM in Chicago found sexual behaviors among AAMSM were more substantially impacted by arrest or incarceration than those of non-black MSM [6].…”
Section: Introductionmentioning
confidence: 99%